A New Technique for the Extraction of Arbuscular Mycorrhizae Fungal Spores from Rhizosphere - Gökhan Boyno; Semra Demir; Younes Rezaee Danesh; Emre Demirer Durak; Rojbin Çevik; Beatrice Farda; Rihab Djebaili; Marika Pellegrini (Journal of Fungi, 2023)
Monitoring the dynamics of the spore bank of arbuscular mycorrhizal fungi (AMF) is essential for the sustainable management and protection of agroecosystems. The most common method for extracting AMF spores from soil is the wet-sieving technique (WST). However, this method has many disadvantages. In this study, we modified the WST using new approaches: the ultrasound wet-sieving technique (UWST) and the ultrasound centrifuge technique (UCT). We enumerated and compared the numbers and quality of spores obtained from WST, UWST, and UCT to validate the new modified techniques. We extracted AMF spores from the rhizospheres of different plants, including wheat (Triticum aestivum L.), bean (Phaseolus vulgaris L.), tomato (Solanum lycopersicum L.), pepper (Piper nigrum L.), parsley (Petroselinum crispum Mill.), and turfgrass (Lolium perenne L.) collected from the Van Lake basin, Turkey. The highest and lowest AMF spore numbers were observed in wheat and turfgrass rhizospheres. The UCT allowed for the extraction of the highest number of spores from all rhizospheres, followed by the UWST and WST. The UWST and WST allowed for the extraction of similar spore numbers from wheat, pepper, parsley, and turfgrass rhizospheres. Beyond the high extracted spore number, UCT was shown to be a fast and low-material-consuming approach. These findings demonstrate that the UCT can be used to efficiently extract AMF spores in future research.